Management of pregnancy in paroxysmal nocturnal hemoglobinuria on long-term eculizumab. Issue 4 (June 2015) - Vekemans, Marie-Christiane; Lambert, Catherine; Ferrant, Augustin; Saussoy, Pascale; Havelange, Violaine; Debiève, Frédéric; Van Den Neste, Eric; Michaux, Lucienne
Abstract : Pregnancy in women with paroxysmal nocturnal hemoglobinuria (PNH) is associated with increased maternal and fetal complications, to such an extent that PNH has for long been considered a relative contraindication for pregnancy. The most serious life-threatening complications are venous thromboembolic events, the risk of which is increased by the hypercoagulable state related to pregnancy. Eculizumab, a C5 complement inhibitor, has revolutionized the treatment of PNH. However, there are no published trials evaluating its use in pregnancy. Most recommendations are based on expert opinions and case reports. We report on the favorable outcome of a PNH patient who became pregnant while under eculizumab, suggesting that this drug can be given from conception to delivery.